Sacrospinous ligament fixation – a Malaysian’s tertiary centre experience - Norlelawati Ab Latip; Ng, PY (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
During the study period from January 2008 to December 2012, 177 women had transvaginal sacrospinous ligament fixation (SSF) for vault suspension at General Hospital Kuala Lumpur. Of the 177 women, 133 (75.1%) had severe uterovaginal prolapse while 44 (24.9%) had post-hysterectomy vault prolapse. All patients with severe uterovaginal prolapse and rectocele undergone vaginal hysterectomy and posterior colporrhaphy respectively. A hundred and seventy-four patients (98.3%) had anterior repair whilst 48 (27.1%) received midurethral sling as concomitant procedure to vault suspension (SSF). The mean duration of surgery was 92.1±30.2 minutes and the mean estimated blood loss was 319±199.3mls. There was no surgical mortality. Two patients (1.1%) had rectal injuries. No patient had bladder injury or de novo urinary symptoms. The commonest immediate postoperative complications was fever (98; 55.4%) followed by buttock pain in 18 (10.2%) patients. Both complications were resolved with conservative measures. Seven patients (3.9%) had sutures erosion as late complications. Of the 177 women, 158 (89.3%) and 141 (79.7%) came for the 6 and 12 months follow-up, respectively. The success rate for all three compartments ranged from 92.4% to 98.1% at 6 months and reduced to range from 85.7% to 94.4% at 12 months. The highest success rate was observed in the posterior compartment followed by apical and anterior compartment. Equally, the recurrence rate was lowest in the posterior compartment (1.9%), followed by the central (3.8%) and anterior compartment (7.5%) at 6 months’ review. This increased to 5.7% for rectocele, 7.8% for vault prolapse and 14.2% for cystocele at 12 months’ follow-up. None had repeated surgery for prolapse recurrence during the study period. In conclusion, SSF remains a high priority in our therapeutic regime for the treatment of severe uterovaginal and vault prolapse as it has a reasonably good success rate with lower serious complications in the skillful hands.